Development Strategy of the Minapolitan Area in East Sei Kepayang District, Asahan Regency - Dedy Armansyah; Abdi Sugiarto (Yayasan Sinergi Multidimensi Kreatif, 2024)
This study aims to examine the Development Strategy of the Minapolitan Area in East Sei Kepayang District, Asahan Regency. The qualitative approach is used because this research aims to dig deeper into the perceptions, views, and experiences of various related parties, including local communities, stakeholders, Data is collected through various relevant qualitative methods, including: In-depth Interview An in-depth interview is conducted to obtain the views, experiences, and perspectives of the main actors involved in the development of the Minapolitan area. To ensure the validity of the data, data triangulation is used, which is comparing and confirming data from various sources (interviews, observations, and documentation). Research Results The development and improvement of fisheries infrastructure, including road access, cold storage facilities, and fish processing centers, is an important step to improve distribution efficiency, maintain product quality, and add added value to fishery products. Strategies to increase access to financing and attract private investment are important elements in overcoming capital constraints. The adoption of modern fisheries technology, both in aquaculture and capture fisheries, is a strategic step that will increase productivity and preserve natural resources. Sustainable management of natural resources, including efforts to preserve aquatic ecosystems and prevent pollution, is an important foundation in ensuring the long-term availability of fish.